Behavioural and psychographic characteristics of supermarket catalogue users. (May 2021) - Tan, Pei Jie; Tanusondjaja, Arry; Corsi, Armando; Lockshin, Larry; Villani, Christopher; Bogomolova, Svetlana
Abstract: Supermarket catalogues (also known as store flyers or circulars) are a popular retail tool for influencing shoppers' behaviour and increasing store sales. Past research has documented varying effects of catalogue promotions on consumer behaviour, but it has not focused specifically on the psychographic and behavioural characteristics of catalogue users. This research aims to fill this gap through an analysis of a representative sample of 506 South Australian consumers. The results show that consumers who use supermarket catalogues are more likely to have one or more of these characteristics: price-consciousness, deal-proneness, low-income, and rarely switches brands. The contribution of this research provides empirical evidence on the user profiles of supermarket catalogues. Retailers and suppliers equipped with this knowledge can create more relevant promotions to increase efficiency and incremental sales.